Cu0.33Co0.67S2 Hexagonal Sheets with 2D Hierarchical Structures for High‐Rate and Long‐Term Lithium Storage. Issue 4 (18th February 2019) - Meng, Yu; Hu, Linfeng; Liu, Handing; Yang, Sangpu; Ruan, Jiafeng; Wu, Haotian; Wang, Pei; Song, Yun; Sun, Dalin; Fang, Fang
Abstract: CoS2 has been studied as a promising anode for lithium ion batteries (LIBs) due to its large capacity and high electrical conductivity. However, CoS2 anodes generally suffer from rapid capacity fading, especially at high rate. Rationally designed morphologies and component tunability offer appropriate approaches to improve its lithium storage performances. Herein, Cu0.33 Co0.67 S2 ultrathin hexagonal sheets with two‐dimensional (2D) hierarchical structure were firstly prepared through a facile and controllable sulfuration strategy from Cu‐doped cobalt hydroxide sheet precursor. The as‐prepared Cu0.33 Co0.67 S2 anode delivers a high reversible capacity of 960 mAh g −1 over 200 cycles at a current density of 1 A g −1 and a stable cycling capacity of 550 mAh g −1 even after 2000 cycles at 10 A g −1 . The excellent electrochemical performances can mainly be attributed to the special 2D hierarchical structure and the synergistic enhancement effect of copper and cobalt ions, which induces reversible decomposition of partial SEI, high pseudocapacitive contributions and fast faradic reaction kinetics. Binary metal sulfide materials combined with a rational hierarchical structure design could provide a promising method to construct high‐performance anodes for applications in electrochemical energy storage. Abstract : Sheet storage : Cu0.33 Co0.67 S2 hexagonal sheets with two‐dimensional (2D) hierarchical structure are prepared through homogeneous precipitation and low temperature sulfuration. The product shows excellent lithium storage properties and long‐term cyclability at high rate, maintaining a stable reversible capacity of 550 mAh g −1 even after 2000 cycles at 10 A g −1 .